Unlocking science Success: How teachers’ understanding and use of learning models boost students' SPS - Norma Yunaini; Mumpuniarti Mumpuniarti; Ishartiwi Ishartiwi; Asih Utami; Mohammad Ghufroni Farid; Yesi Budiarti; Riyan Hidayat (Social Sciences and Humanities Open)
SPS are crucial in science education, as they form the foundation for enhancing students' thinking skills, which are essential for navigating 21st-century developments. Teachers play a pivotal role in implementing effective learning activities. This study examines the impact of elementary school teachers' understanding and use of various science models learning on students' SPS. A quantitative research method with a predictive correlational design was used, analyzed using structural equation modeling (SEM) with SmartPLS 4 software. The findings indicate that teachers' comprehension and use of different science models learning have a positive and significant effect on elementary students' SPS. The results show that, through the use of appropriate and engaging science learning models, elementary students are beginning to demonstrate notable progress in self-development, as measured by SPS indicators. It is anticipated that using a variety of science models learning tailored to the characteristics of elementary students will further enhance their development of SPS (SPS).